Applications of Marketing Information System in Banking Sector: A Study on VakÄ±fBank - KoÃ§oÄŸlu, Duygu; Yilmaz, Mustafa Atahan; Kayhan, Murat (European Scientific Journal, ESJ, 2017)
Marketing managers have discovered importance of information and information-based marketing system for a long time. They have realized that information is a tool which can change the competition conditions. Companies may gather required information by itself or outsourcing. It is known that many problems have been occurred on information gathering and using process. The purpose of this study is to examine concept of Marketing Information System by literature review and to reveal issues of banking sector applications on information gathering and using. Semi-structured interviewing which is one of the qualitative research methods was used in this study. Implications are discussed and recommendations are given for the banking sector.